The The Use of Instagram for Promoting Private Higher Education In Jakarta Indonesia : The Use of Instagram for Promoting Private Higher Education In Jakarta Indonesia - Marwa Ulfa; Farida Hariyati; Deni Adha Akbari (Mediator: Jurnal Komunikasi, 2023)
Muhammadiyah University prof. DR. HAMKA (UHAMKA) is an Indonesian university that uses social media to spread information in the digital age. This research seeks to comprehend UHAMKA's use of Instagram as a promotional medium. This study employs a descriptive-based qualitative approach to big data, with in-depth interviews, documentation, and literature reviews as data-gathering techniques. The findings of the study indicate that the following factors have the most significant impact on the performance of the content on Instagram: (1) Type of media: According to research, images tend to perform better than videos in terms of engagement and reach; (2) Formats: albums tend to perform better than other formats, such as stories or reels; (3) The theme raised has a significant impact on engagement; (4) Emotion: Content that makes people feel happy, inspired, or amused is typically superior to other types of content; and (5) Theme: the theme raised has a significant impact on engagement. (5) Consistency: It is crucial to be constant with posting frequency and timing to maintain interest and expand reach.